Patterns of Feedback Used in the E-Learning System from the Teachers of the First Cycle in the Governorate of Muscat at the Sultanate of Oman (Journal Of Educational and Psychological Researches, 2023)
AbstractThis study aims to identify the degree to which the first cycle teachers use different feedback patterns in the e-learning system in addition to the differences in the degree of use according to specialization, teaching experience, and in-service training in the field of classroom assessment, as well as the interaction between them. The study sample consisted of (350) female teachers of the first cycle in government schools in Muscat Governorate for the academic year 2020/2021. The study used a questionnaire that contained four different patterns of feedback, which are reinforcement, informative, corrective, and interpretive feedback. The psychometric properties of the questionnaire were verified in terms of validity and reliability. Among the most prominent findings of the study that reinforcement feedback was the most frequently used feedback pattern from the teachers of the first cycle compared to the informative feedback was the least used. Also, there were statistically significant differences between the teachers in the degree of use of feedback patterns in terms of variables of specialization and teaching experience. On the other hand, there were no statistically significant differences between the teachers in the degree of use of feedback patterns due to the in-service training in the field of classroom assessment and the 2-way interactions between the variables. The study concluded with a set of recommendations and suggestions, including emphasizing the importance of female teachers to employ different feedback patterns for students in the process of continuous assessment and conducting more studies on different feedback patterns and their effectiveness at various educational levels and subjects.